Evaluation of methods for determining crack initiation stress under compression - Wen, Tao; Tang, Huiming; Ma, Junwei; Wang, Yankun (Engineering geology, 2018)
The accurate determination of crack initiation stress (CI) is significant for understanding rock deformation and failure. In this paper, a new concept is introduced, namely the relative compression strain response (RCSR), which represents the compressive deformation of the rock before dilatancy of the rock is introduced. An RCSR-based method for determining CI is proposed and compared with existing methods, i.e., (1) the volumetric strain (VS) method, (2) the lateral strain (LS) method, (3) the crack volumetric strain (CVS) method, (4) the cumulative acoustic emission hit tangent (CAEHT) method, and (5) the lateral strain response (LSR) method. Data for the comparison are collected from 227 uniaxial compression test and 222 compression test for diverse rock types. The comparison results show that, the CI determined using the proposed method is in good agreement with that determined using the existing methods. The CI values determined using different methods are similar, at approximately 0.5 of uniaxial compressive strength (UCS). The ratio of CI to peak strength (PS) is approximately 0.55 under triaxial compression, which is greater than the CI/UCS ratio. According to the analysis of variance (ANOVA), there is no statistical difference among the existing methods. Compared with the exisiting methods, the proposed method has advantages of avoiding users judgment subjectivity Thus, the RCSR method can be employed to determine the CI under uniaxial and triaxial compression. •The relative compression strain response (RCSR) method to determine the CI is proposed.•An amount of uniaxial and triaxial compression tests for different rock samples data from the literature were collected.•The CI/UCS ratio in uniaxial compression and the CI/PS ratio in triaxial compression are analyzed.